Draft Genome Sequence of Xylaria longipes DSM 107183, a Saprotrophic Ascomycete Colonizing Hardwood - Büttner, Enrico (Microbiol Resour Announc, 2019)
The saprotrophic soft-rot fungus Xylaria longipes was isolated from deadwood of Acer pseudoplatanus collected in the Bavarian Forest, Germany. The whole genome of this strain (DSM 107183) was sequenced with a total size of 43.2 Mb and a G+C content of 48.5%. The genome comprises 12,638 predicted coding sequences.